Cancer Therapy-Related Cardiac Dysfunction: An Overview for the Clinician. Issue 13 (July 2019) - Perez, Irving E; Taveras Alam, Sara; Hernandez, Gabriel A; Sancassani, Rhea
Cancer therapy-related cardiac dysfunction (CTRCD) is one of the most feared and undesirable side effects of chemotherapy, occurring in approximately 10% of the patients. It can be classified as direct (dose-dependent vs dose-independent) or indirect, either case being potentially permanent or reversible. Risk assessment, recognition, and prevention of CTRCD are crucial.